2020
DOI: 10.1001/jamapsychiatry.2019.3474
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Stellate Ganglion Block Treatment on Posttraumatic Stress Disorder Symptoms

Abstract: IMPORTANCE This is the first multisite, randomized clinical trial of stellate ganglion block (SGB) outcomes on posttraumatic stress disorder (PTSD) symptoms.OBJECTIVE To determine whether paired SGB treatments at 0 and 2 weeks would result in improvement in mean Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) total symptom severity scores from baseline to 8 weeks. DESIGN, SETTING, AND PARTICIPANTSThis multisite, blinded, sham-procedure, randomized clinical trial used a 2:1 SGB:sham ratio and was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 38 publications
2
98
0
Order By: Relevance
“…Clinical symptoms and psychological scale scores of patients with PTSD treated with SGB improved considerably, with patients sleeping better and remaining in a more stable emotional state than before treatment. 4,5 Our patient exhibited a marked improvement in sleep after receiving SGB, indicating that even for patients with a complicated and severe clinical presentation, SGB can provide visible benefits.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Clinical symptoms and psychological scale scores of patients with PTSD treated with SGB improved considerably, with patients sleeping better and remaining in a more stable emotional state than before treatment. 4,5 Our patient exhibited a marked improvement in sleep after receiving SGB, indicating that even for patients with a complicated and severe clinical presentation, SGB can provide visible benefits.…”
Section: Discussionmentioning
confidence: 69%
“…SGB has been used to treat this disorder and relieve sympathetic hyperactivity in the long term. 4,5 This fast-acting, somatic approach can reduce the barriers that prevent patients from receiving therapy, which are frequently encountered in the treatment of anxiety and insomnia, 6 particularly among the military population. Most patients who benefit from SGB present with only one or two symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A small sample of these cases is documented in the literature primarily in level 3 studies, yet if the collective results are considered in entirety, they show great consistency in SGB effects. There are 14 original studies published since 1990 in the peer‐reviewed medical literature documenting SGB’s successful treatment of PTSD symptoms (Alino, Kosatka, McLean, & Hirsch, 2013; Alkire et al., 2014; Alkire et al, 2015; Hanling et al., 2016; Lebovits, Yarmush, & Lefkowitz, 1990; Lipov, Joshi, Lipov, Sanders, & Siroko, 2008; Lipov et al., 2012, 2013; Lynch et al., 2016; McLean, 2015; Mulvaney et al., 2014; Mulvaney, Lynch, de Leeuw, Schroeder, & Kane, 2015; Mulvaney, McLean, & De Leeuw, 2010; Rae Olmsted et al, 2020). In November 2019, a large multicenter, randomized clinical trial demonstrated twice the effect of SGB over a sham procedure (Rae Olmsted et al, 2020).…”
Section: Neuroscience‐informed Treatmentmentioning
confidence: 99%
“…Stellate ganglion block (SGB) is a technique unique to the Department of Anesthesia, which plays an unparalleled role in the treatment of many diseases. [6][7][8] The TLR4/NF-κB pathway is also a classic in ammatory pathway. 9 It has been reported that SGB can signi cantly reduce the in ammatory response.…”
Section: Introductionmentioning
confidence: 99%